The Role of Fisherwomen in Improving the Economy and Education of the Family in Kampung Bugis Village, Tanjungpinang City - Saniah, Mahfuzah; Zulfah, Zulfah; Ulfa, Anisa (TANJAK, 2023)
Tanjungpinang is an area consisting of islands, most of which are coastal, where the people make their living as fishermen which is still related to the problem of community poverty and has become a phenomenon from year to year in coastal areas. Fisherwomen can create empowerment for coastal communities. In this discussion, the fisherman's wife is one of the household members who can increase the family income. This research is qualitative research with data collection techniques through observation, and historical interviews and supported by documentation. Interviews were conducted with fisherwomen in Bugis Tanjungpinang Village. The results of this research show that women who live in coastal areas, especially the Bugis Village area, have an influential role in increasing family income and quality of education. The results of fishing women's income can be seen from the fulfillment of primary and secondary needs including tertiary needs. The husband and wife relationship can meet the needs of the family by working together to improve family welfare. Another thing that can be seen is the quality of family education which has increased as many generations have continued their education. The husband and wife relationship can meet the needs of the family by working together to improve family welfare. Another thing that can be seen is the quality of family education which has increased as many generations have continued their education. The husband and wife relationship can meet the needs of the family by working together to improve family welfare. Another thing that can be seen is the quality of family education which has increased as many generations have continued their education.